Thesis Camp As An Effort To Complete The Student's Final Project (Tesis) Of The Unimus Nursing Master’s Degree Program During The COVID-19 Pandemic - Pohan, Vivi Yosafianti; Alfiyanti, Dera (University of Muhammadiyah Semarang, 2022)
This research is a research and development that aims to develop technical thesis learning by using thesis camp as one of the learning techniques in preparing a thesis proposal for Unimus nursing masters students. The technical development of this learning is based on the length of time it takes to complete a thesis proposal experienced by most of the Unimus master's nursing students who are preparing a thesis proposal. The results of the survey on students showed that 85% had difficulty in compiling a thesis proposal for various reasons, including difficulty finding the research title, difficulty finding problems, and difficulty managing time because most of the students were already working. This has an impact on the length of the student's study period which affects the discrepancy with the educational calendar. This study was designed to: 1) examine students' understanding in the preparation of a thesis proposal, 2) create a technical prototype for thesis camp learning, 3) test the effectiveness of the thesis camp, and 4) compile a thesis camp guidebook. This research generally uses a research and development approach. The research stages used descriptive qualitative methods in exploratory studies, and development through workshop activities in the context of preparing a camp thesis guide book. During the COVID-19 pandemic, it was not possible for students to consult directly with the thesis supervisor, so this thesis camp was carried out with blended learning (70% online learning and 30% learning offline) and while offline still using the Covid-19 prevention protocol, consist of here are wearing masks, washing hands, and keeping a distance. Thesis camp is proven to be effective in increasing the timeliness of completing thesis writing for nursing master students of Unimus.